Pariwisata Berbasis Syariah (Telaah Makna Kata Sara dan Derivasinya dalam al-Qur’an) - Rahmi Syahriza (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2014)
Tourism is one of the means of developing the concept of Islamic economics is taken from the Koran. Allah has given human gesture to take a trip whose purpose is to strengthen the faith and confidence as well as to provide motivation. With the gesture is at least could pave the way for the development of sharia -based businesses other than banking.